..........................................
Anexe:
Răspunsuri la întrebare
Răspuns de
0
Incercam asa :
[tex]4-(x-1)^2 =2^2-(x-1)^2=[2-(x-1)][2+(x-1)] =(2-x+1)(2+x-1)=(3-x)(1+x)[/tex]
[tex]4-(x-1)^2 =2^2-(x-1)^2=[2-(x-1)][2+(x-1)] =(2-x+1)(2+x-1)=(3-x)(1+x)[/tex]
Alte întrebări interesante
Informatică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Biologie,
9 ani în urmă